Mineralogical and geochemical properties of mudstones in the Maden Complex around Elazig and Bingöl (Turkey) - Koprubasi, Necla; Aydin, Betul; Ustundas, Nazli; Simoes, Emel Bacha; Konakci, Nevin; Sasmaz, Ahmet (Nature Portfolio, 2026)
The mudstones within the Maden Complex exhibit extensive outcropping in the Elazig and Bing & ouml;l regions, T & uuml;rkiye. The P & uuml;t & uuml;rge Metamorphics (Paleozoic), Guleman Ophiolites (Jurassic-Lower Cretaceous), Maden Complex (Middle Eocene), and Lice Formation (Lower-Middle Miocene) are exposed in the region. The mudstones are found around Palu (Elaz & imath;& gbreve;) and Gen & ccedil; (Bing & ouml;l), with thicknesses ranging from 150 to 200 m in Palu and 60-70 m in Gen & ccedil;, and are inclined at approximately 15 degrees to the north. Analysis of twenty samples revealed that the Gen & ccedil; mudstones are predominantly composed of SiO2, MgO, Fe2O3, and CaO, while the Palu mudstones are composed of SiO2, Al2O3, CaO, MgO and Fe2O3. These mudstones show enrichment in trace elements Cr, Co, Ni, and As, while other trace elements show a decrease. The average Sigma REE content of the mudstones in the region is 6.84 ppm in the Gen & ccedil; mudstones and 60.8 ppm in the Palu mudstones. Similarly, when normalized to chondrites, light rare earth elements (LREE) enrichment is observed, while in the graph normalized with PAAS, the enrichment of heavy rare earth elements (HREE) is evident. The Maden Complex mudstones exhibit positive Ce and Eu anomalies in their rare-earth element (REE) patterns. The only redox-sensitive REE is cerium, and oxidation-reduction reactions in marine settings have a significant influence on its behavior. Ce3(+) is easily oxidized to the insoluble Ce4(+) under oxidizing circumstances and is mostly eliminated by Fe-Mn oxyhydroxides, which causes its accumulation in the sediments and the formation of a positive Ce anomaly. The observed positive Ce anomaly indicates that deposition most likely occurred in an aerated, relatively open marine basin with well-oxygenated bottom water. A positive Eu anomaly, on the other hand, indicates a distinct type of control that is frequently connected to hydrothermal processes or high-temperature water-rock interactions. Positive Eu anomalies are thought to be a reliable sign of hydrothermal input and are frequently observed in hydrothermal deposits and metal-bearing sediments. Consequently, the coexistence of positive Ce and Eu anomalies points to a complicated depositional system in which hydrothermal or volcanic contributions coexisted with oxygenated seawater conditions. As shown in both contemporary and ancient oceanic environments, these geochemical markers are consistent with depositional activity in a tectonically active marine basin driven by underwater hydrothermal activity. The paleoclimate, weathering, paleosalinity, water characteristics in the depositional environment, depositional depth, and the presence of hydrothermal input indicate that the mudstones were likely deposited in a marine environment dominated by saline and brackish water, with abundant hydrothermal contributions, warm and oxygenated conditions. Furthermore, based on the main oxide and trace element contents of the lithological units in the region, the basement material of Gen & ccedil; mudstones consists mainly of MgO and SiO2 with high Ni, Co, and Cr content and low REE content, while Palu mudstones consist of SiO2, Al2O3 and CaO with high V, Cu, Rb, Sr, and REE content. This supports the idea that Gen & ccedil; mudstones likely originated from serpentine rocks associated with the Guleman Ophiolites in the region, while Palu mudstones may have been fed by silica and clay units belonging to the P & uuml;t & uuml;rge Metamorphites, which have extensive outcrops in the area. The significant geochemical differences observed between the Gen & ccedil; and Palu Basins indicate that the Maden Basin is not a uniform depositional environment, but rather consists of sub-basins divided into sections with fundamentally different sedimentary sources and redox dynamics.
Keywords: Maden Complex; Mudstone; Mineralogy; Geochemistry; Paleoenvironmental Characteristic; Tectonic Environment